A technique for taping inferior vena cava caudal to the duodenum: duodenal penetration by IVC filter strut after retroperitoneal lymph node dissection—usefulness of the mesenteric approach - Shimizu, Takayuki (Surg Case Rep, 2019)
BACKGROUND: Although an inferior vena cava (IVC) filter is used for preventing pulmonary thromboembolism (PTE) in patients with deep vein thrombosis, IVC filter penetration in the duodenum is a rare complication. CASE PRESENTATION: A 35-year-old man had previously undergone retroperitoneal lymph node dissection (RPLND) for testicular cancer and IVC filter placement for prevention of PTE. Esophagogastroduodenoscopy (EGD) for his epigastric pain revealed penetration of the IVC filter in the duodenum. The IVC filter was retrieved through cavotomy, and the duodenal penetration was repaired using EGD clipping. Although it was difficult to mobilize the duodenum due to adhesion resulting from RPLND, the use of a mesenteric approach enabled encircling of the IVC caudal to the duodenum. The mesenteric approach is useful and safe for taping the IVC caudal to the duodenum in cases where it is difficult to mobilize the duodenum. CONCLUSION: IVC taping using the mesenteric approach allowed safe retrieval of the IVC filter after RPLND without postoperative complications.